A INFLUÊNCIA DA COMPATIBILIDADE PESSOA-TRABALHO SOBRE O ENGAJAMENTO NO TRABALHO SÃO BERNARDO DO CAMPO 2015 - Carvalho, Silvia Regina de (2015)
The engagement at work is one of the goals of the peoples managers. This study aims to examine if the compatibility of the person with the working environment is related to their engagement. There are three factors in compatibility with the working environment (person-environment fit): person-job fit, which addresses the compatibility between the skills of the person and the work it executes; person-organization fit, which is related to the personal values compared to the organizations values; and needs-supply, which addresses the individuals perception as to have their needs met by their work and the organization where he works. Constructs of organizational behavior such as job satisfaction, organizational commitment and turnover intentions are commonly used as successor variables in compatibility studies (fit) however, no studies about the relationship between work environment compatibility (person-environment fit) and engagement at work were found. This quantitative research approach was based on the Perceptions Fit instrument proposed by Cable and DeRue in 2002; and UWES instrument - Ultrech Work Engagement Scale of Schaufelli and collaborators, 2006. We studied 114 respondents with at least six months in the current activity and at least five years in the labor market. The analyses by Structural Equation Modeling by PLS (Partial Least Squares) method support the hypothesis that the greater the compatibility between the person and his work, the greater their engagement. In addition to the central hypothesis of the work that the person-job compatibility influences the engagement at work, the influence of fit dimensions on engagement were tested and the results showed that the needs-supply dimension has the most influence on engagement. This study starts the discussion on the relationship between a persons compatibility with the work environment and their engagement, suggesting reapplication of the method in different audiences, so that the results can be used for